Identifikasi Serangga Hama Pada Tanaman Kopi Robusta Di Desa Mojorejo Kecamatan Selupu Rejang Kabupaten Rejang Lebong - Ningrat, Bayu Cahya; Darwan Effendi; Venti Novitasari; Muslim; Lasmi (PUCUK : Jurnal Ilmu Tanaman, 2025)
Mojorejo Village is one of the villages in Selupu Rejang District, Rejang Lebong Regency. The majority of the Mojorejo Village community cultivates many robusta coffee plants, the Sintaro clone. In practice in the field, most robusta coffee plants are attacked by insect pests. This causes the productivity and income of coffee farmers in Mojorejo Village to be less than optimal. The purpose of this study was (1) to identify the types of insect pests that attack Robusta coffee plants in Mojorejo Village, (2) to determine the characteristics of the identification of insect pests of robusta coffee plants in Mojorejo Village. The research method used is a descriptive exploratory approach. The results of this study have found 5 orders of insect pests and are divided into 17 families, insect pests of coffee plants in Mojorejo Village have different characteristics, these insects suck, bite, make holes, tear, and make homes in coffee plants. This study is expected to provide information to the community about insect pests in plants and help control both biologically and chemically which can later increase coffee plant production.